Implementasi Pendidikan Holistik Berbasis Integrasi Sains dan Keagamaan di PSDKU Universitas Brawijaya Kota Kediri - Muhammad Ichsan Yahya; M. Khamim; Suko Susilo (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aims to analyze the implementation of holistic education based on the integration of science and religion at PSDKU Universitas Brawijaya Kediri. Holistic education emphasizes the development of humans as complete individuals, covering cognitive, affective, psychomotor, social, and spiritual domains. The integration of science and religion in higher education serves as a strategic effort to cultivate intellectual competence alongside moral and religious awareness. This study employed a qualitative research design with data collected through observation, interviews, and documentation. The findings show that the integration has been realized through curriculum design that incorporates religious values, student-centered learning models, and campus organizational activities that nurture ethical and spiritual character. In addition, lecturers play a role as facilitators who encourage reflective thinking, scientific inquiry, and moral responsibility. Meanwhile, student organizations contribute to the formation of religious culture on campus through mentoring, discussions, and faith-based community activities. The implementation of holistic education at PSDKU UB Kediri contributes positively to shaping students’ identity as intellectually strong and morally conscious individuals. This research highlights the importance of harmonizing scientific understanding and religious values in developing an educational environment that not only produces knowledgeable graduates but also responsible and ethical members of society.